CAN ELECTION JUSTICE AND ECO-JUSTICE BE ACHIEVED SIMULTANEOUSLY THROUGH SUPERVISORY? A CASE STUDY OF REGIONAL ELECTIONS IN WEST JAVA INDONESIA - Anjani, Nisrina Khansa (Bawaslu Provinsi Jawa Barat, 2024)
The intersection of election justice and eco-justice is an emerging area of focus, highlighting the connection between democratic processes and environmental sustainability. As societies grapple with environmental challenges and increasing social inequalities, the 2024 elections present an opportunity to address both issues simultaneously. This paper investigates the environmental impact of the 2024 Pilkada Serentak (simultaneous regional elections) in Indonesia, with a specific focus on the environmental consequences of the election materials used throughout the process. It analyzes key materials such as paper ballots, election booths, and ballot boxes, as well as the carbon emissions generated during the distribution of these materials to 27 regencies and cities in West Java. The study employs a Life Cycle Assessment (LCA) framework to assess the environmental footprint of these materials, considering all stages from production and transportation to disposal. The analysis provides a comprehensive evaluation of the ecological impact associated with the logistics of the election process, including the emissions related to the transportation of materials and the waste generated from non-biodegradable election materials. Drawing from the findings, this paper offers a set of policy recommendations aimed at reducing the environmental impact of future elections.